Assessment of prevalence and epidemiological determinants of undernutrition in children of 6-60 months of the age in an urban slum of Mumbai, India - Kumar, Pankaj; Kembhavi, R.; G., Prahatheeswaran (International Journal Of Community Medicine And Public Health, 2024)
Background: In urban slums, several socio-demographic factors contribute for the occurrence of undernutrition in children of 6-60 months of the age, this study aims at Assessment of prevalence of undernutrition in children of 6-60 months of the age in an urban slum of Mumbai and to study associated factors. Methods: A cross-sectional study was conducted in Urban Slum which is a field practice area of institution. Children of 6-60 months of the age were included in the study and information was gathered by interviewing parents/caretakers and anthropometric measurement of all children confirming to the inclusion criteria were recorded. Data was analysed with SPSS v.22.0 with suitable tests. Results: Prevalence of undernutrition was found 50.6%, more per cent of undernutrition was found in 25-60 months age 100 (54.1%), 90 (53.3%) girls, 132 (51%) nuclear family dwellers, in 43 (64.2%) children whose mothers got married <18 years age. 88 (71.5%) children with undernutrition belonged to Class IV, (B.G Prasad classification), statistically significant association of undernutrition was found with the factors age of child, mother’s education, birth order, birth weight, immunisation status, mother’s age at marriage, exclusive breast feeding, history of acute respiratory infection (ARI) and diarrhoea, and socio-economic status. Conclusions: Study found certain socio-demographic factors like age, gender and birth order of child, type of family, age of mother during marriage and her literacy level, exclusive breast feeding, immunisation and frequency of ARI and diarrhoea associated with undernutrition.